2002
DOI: 10.1016/s0006-3207(02)00088-5
|View full text |Cite
|
Sign up to set email alerts
|

Simulating anthropogenic impacts to bird communities in tropical rain forests

Abstract: We used an aggregated modelling approach to simulate the impacts of anthropogenic disturbances on the long-term dynamics of faunal diversity in tropical rain forests. We restricted our study to bird communities even though the approach is more general. We developed a model called BioDiv which simulated the establishment of hypothetical bird species in a forest. Our model was based on the results of a simple matrix model which calculated the spatio-temporal dynamics of a tropical rain forest in Malaysia. We ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 82 publications
0
15
0
Order By: Relevance
“…However, even low levels of timber extraction can result in damage to 40-70% of the canopy due to the construction of roads and skid trails (Johns et al, 1996;Webb, 1997). In modelling the gap environment under additive edge effects, Malcolm (1998) found disproportionate changes in gap environments even at low harvest levels, a result echoed in Kohler et al (2002), who hypothesized strong changes in bird communities even at low harvest intensities. Based on cumulative edge effects, Struhsaker (1997) concluded that the threshold level of canopy damage might be as little as 5%.…”
Section: Introductionmentioning
confidence: 97%
“…However, even low levels of timber extraction can result in damage to 40-70% of the canopy due to the construction of roads and skid trails (Johns et al, 1996;Webb, 1997). In modelling the gap environment under additive edge effects, Malcolm (1998) found disproportionate changes in gap environments even at low harvest levels, a result echoed in Kohler et al (2002), who hypothesized strong changes in bird communities even at low harvest intensities. Based on cumulative edge effects, Struhsaker (1997) concluded that the threshold level of canopy damage might be as little as 5%.…”
Section: Introductionmentioning
confidence: 97%
“…However, 32% of all studies were conducted >20 years after logging disturbance. The only study representing a much longer time period (> 50 years) used a theoretical rather than empirical modelling approach [38]. …”
Section: Potential Sampling Biasesmentioning
confidence: 99%
“…Therefore, we cannot exclude that even small changes in the abundance of a particular species may have large impacts on the forest ecosystem as a whole, e.g. due to bird species feeding on a certain species (Köhler et al, 2002). Now we calculate for each scenario S i a score V SC1 ðS i Þ which is the average of the scaled values v 3 ðS i Þ; v 4 ðS i Þ; and v 5 ðS i Þ: This score measures the performances of the scenario S i in criterion SC1 (note that by using the average in the aggregation of indicators I 3 -I 5 we assume that each of these indicators has equal weight).…”
Section: Indicators and Multicriteria Decision Analysismentioning
confidence: 99%